2020
DOI: 10.1155/2020/5612486
|View full text |Cite
|
Sign up to set email alerts
|

Nauclea latifolia Sm. Leaf Extracts Extenuates Free Radicals, Inflammation, and Diabetes-Linked Enzymes

Abstract: This study was carried out to assess the in vitro antioxidant, anti-inflammatory and antidiabetic effects of Nauclea latifolia (Sm.) leaf extracts. Ethanolic (NLE) and aqueous (NLA) extract of N. latifolia leaves were prepared and assessed for their anti-inflammatory activity, antioxidant potential, α-amylase and α-glucosidase inhibitory activities, and the mechanism of enzyme inhibition in vitro using standard established methods. From the results, phytochemicals such as flavonoids, phenolics, glycosides, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
1
23
1
Order By: Relevance
“…The geographical distribution between malaria and viral diseases where malaria endemic regions of the world such as Africa and Asia appear to experience relatively low cases of COVID-19-related mortalities led to the consideration of a possible therapeutic convergence between antimalarial plants (which have continued to be used against malaria in Africa) and viral pathogens including the dreaded SARS CoV-2. One possible explanation attributable to this unresolved therapeutic convergence is the mechanism of activity of these medicinal plants; several antimalarial phytomedicines which tend to produce more bioactivity as antioxidants, anti-inflammatory and immunomodulatory may function both as antimalarials and antiviral since the underlying mechanism of activity is not directly targeting the pathogen but rather boosting the immunity of the host, effective and efficient resolution of early inflammatory/anti-inflammatory cytokines ( Afolayan et al, 2020 ) and scavenging of generated lethal free radicals ( Iheagwam et al, 2020 ). This school of thought has been put forward to explain why many widely used African phytomedicines have gained more anecdotal claims of efficacy yet they do not easily kill the malaria parasite in vitro but produce good in vivo activity.…”
Section: Methodsmentioning
confidence: 99%
“…The geographical distribution between malaria and viral diseases where malaria endemic regions of the world such as Africa and Asia appear to experience relatively low cases of COVID-19-related mortalities led to the consideration of a possible therapeutic convergence between antimalarial plants (which have continued to be used against malaria in Africa) and viral pathogens including the dreaded SARS CoV-2. One possible explanation attributable to this unresolved therapeutic convergence is the mechanism of activity of these medicinal plants; several antimalarial phytomedicines which tend to produce more bioactivity as antioxidants, anti-inflammatory and immunomodulatory may function both as antimalarials and antiviral since the underlying mechanism of activity is not directly targeting the pathogen but rather boosting the immunity of the host, effective and efficient resolution of early inflammatory/anti-inflammatory cytokines ( Afolayan et al, 2020 ) and scavenging of generated lethal free radicals ( Iheagwam et al, 2020 ). This school of thought has been put forward to explain why many widely used African phytomedicines have gained more anecdotal claims of efficacy yet they do not easily kill the malaria parasite in vitro but produce good in vivo activity.…”
Section: Methodsmentioning
confidence: 99%
“…Doty ex Silva (Solieriaceae) and Corallopsis opuntia J. Agardh (Hypneaceae) extracts have been observed to be more effective than M. latifolia extracts (Makkar and Chakraborty 2017). All the IC 50 of the positive controls used in the study were compared with literature and the validity of the assays were supported (Mzid et al 2017;Iheagwam et al 2019aIheagwam et al , 2020Budipramana et al 2019;Sarac et al 2019). The present study showed that the isolated compounds 1-4 inhibited a-amylase and thus contributed to the a-amylase inhibition activity of the M. latifolia chloroform extract.…”
Section: Discussionmentioning
confidence: 99%
“…After standing for 30 minutes, the decrease in absorbance of test mixtures was read at 517 nm. 25,26 The scavenging effect was calculated using the following expression:…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…IC 50 was determined. 25,26 Chromatography. The crude extract adsorbed with silica gel at concentration 1:5 (W/W) was subjected to vacuum liquid chromatography (VLC) on silica gel dry packed column 27 using the solvents n-hexane, ethyl acetate and methanol in a gradient ratio of 100%, 75%:25%, 50%:50%, and 25%:75% (V/V) which yielded nine fractions.…”
Section: Meterials and Methodsmentioning
confidence: 99%